Chronic cannulation in the small intestine of feral pigeons (Columba livia) to assess bioavailability - J.G. Chediack; F.D. Cid; S.V. Fasulo; E. Caviedes-Vidal (Veterinární Medicína, 2010)
We improved a method of chronic duodenal cannulation to study intestinal transport of solutes in an in vivo model (pigeon, Columba livia). A hypoallergenic cannula was inserted into the proximal part of the small intestine of pigeons and used for solution administration. Recovery from surgery was extremely rapid and animals started eating and drinking within a day. After surgery, the body mass of cannulated pigeons was stable, and no adverse effects in the weight could be detected. The method is simple, economical and useful to determine intestinal bioavailability of solutes, for nutritional and ecological studies, in intact animals without influence of anesthesia.